2014
DOI: 10.4103/0970-1591.142055
|View full text |Cite
|
Sign up to set email alerts
|

Practical approach to screen vesicoureteral reflux after a first urinary tract infection

Abstract: Introduction:Vesicoureteral reflux (VUR) is a common pediatric urologic disorder. After the first urinary tract infection (UTI), imaging studies are recommended, starting with a renal ultrasound (RUS). Voiding cystourethrography (VCUG) and dimercaptosuccinic acid (DMSA) scan are the other main radiologic studies used to detect VUR. We evaluated the use of RUS as a screening method for VUR in children below 2 years of age, in order to avoid unnecessary VCUG.Materials and Methods:Medical records and imaging stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Several other studies have pointed out the same finding and have concluded that cystourethrography is indicated in only patients with DMSA abnormalities [2]. This methodology has high sensitivity and negative predictive value in the detection of high grade VUR (86% and 93% respectively) [2,3]. The Visualization of the dilated collecting system in DMSA scintigraphy has never been analyzed previously.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Several other studies have pointed out the same finding and have concluded that cystourethrography is indicated in only patients with DMSA abnormalities [2]. This methodology has high sensitivity and negative predictive value in the detection of high grade VUR (86% and 93% respectively) [2,3]. The Visualization of the dilated collecting system in DMSA scintigraphy has never been analyzed previously.…”
Section: Introductionmentioning
confidence: 74%
“…Recent studies have indicated another potential benefit of DMSA scan to pick patients who need further imaging by voiding for diagnosis of VUR [2,3]. None of the patients with normal DMSA scintigraphy had high grade VUR according to these reports.…”
Section: Bilateralmentioning
confidence: 81%
“…Abnormal renal US results also showed a statistically significant association with VUR after a first febrile UTI in children. 26,27 Fuente et al 28 reported that 98% of children with normal renal US results after a first febrile UTI had no or low-grade VUR (grades I and II VUR), and VCUG should be considered only in children with abnormal findings on renal US. The negative predictive value of renal US for identifying VUR was 90% in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…La cistoutretrografía miccional (CUGM), es el método de oro para detectar RVU, pero requiere cateterización uretral que es dolorosa, conlleva un (17) riesgo de infección y produce irradiación. La Academia Americana de Pediatría no recomienda la prescripción de CUGM en forma rutinaria después de la primera ITU, excepto en caso de detección ecográfica de hidronefrosis, uropatía obstructiva, u otros tipos de anomalías como (18) cicatrices renales o en ITU atípica , a pesar de que la ecografía no es un buen método para detectar RVU porque ésta puede ser normal en RVU debajo grado, y en los de alto grado puede demostrar signos indirectos como dilatación ureteral o hidronefrosis.…”
Section: Discussionunclassified